2019
DOI: 10.3390/su11247028
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Thinking Model to Support Long-Term Bearability of the Healthcare System: The Case of the Province of Quebec

Abstract: This paper describes the modeling efforts devoted by the Ministry of Health and Social Services of Québec, Canada (MSSS), to ensure the long-term bearability of their care system. To this end, it studies the relationships between four entities that self-regulate and interact to form the complex care-providing system: (1) universities; (2) hospitals and doctors; (3) the ministry; and (4) society. The first phase of this research focuses on modeling such relationships and relies on the system dynamics methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Given the complexity of the existing mathematical models, as well as the nomenclature used in the development of the solutions, the graphical user interface generated a more adequate understanding and interactions between the user and the computer [15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the complexity of the existing mathematical models, as well as the nomenclature used in the development of the solutions, the graphical user interface generated a more adequate understanding and interactions between the user and the computer [15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The solution based on a graphical interface in Lagarda-Leyva and Ruiz [29] and Arana et al [30] allows the critical data to be concentrated in a clear and structured way for the users. A graphical interface is formed by the graphic elements that allow fluid communication between a system or structure and the interested user.…”
Section: Empirical Studies Related To This Researchmentioning
confidence: 99%
“…The authors in [24] reported recommendations on the potential of system thinking modeling in the use of causal loops; one of the phases in the system dynamics methodology encompassed the development of a causal model, considering exogenous and endogenous variables, as well as parameters that directly impact the behavior of one or more dynamic variables within the entities.…”
Section: Empirical Studiesmentioning
confidence: 99%